Challenges And Expectation For Implementation Of Technical And Vocational Education Training (TVET) In Malaysian Prison Institutions: A Preliminary Study - Afzamiman Aripin , Muhamad; Rizal Ramly, Mohd; Fahmi Adnan, Mohd; Rasidi Pairan, Mohamad (KnE Social Sciences, 2022)
The Malaysian Prison Department offers rehabilitation programmes for inmates that include guidance and counselling, disciplinary, religious and moral education, vocational and skills training and pre-release programs before they return to society as law-abiding citizens, and the success of this program is based on the recidivism rate. Implementation of Technical dan Vocational Education Training (TVET) in the Human Development Program (PPI) depends on the professional development of the instructor and must be in line with the national level requirement. Prison vocational instructors need to possess different teaching competencies due to their unique environment. This study aimed to identify and provide a new approach for training vocational teachers according to the needs of different stakeholders such as instructors, trainers (inmates) and related parties involved in TVET training. This study used a qualitative approach to collect the data. It used a semi-structured interview strategy with the educational experts in TVET, including training module developers, teaching experts, national industrial experts, prison senior officers, NDTS coaches, NDTS trainers and NDTS coordinators. The interview was to develop in-depth knowledge to enhance the data on the important domains of teaching competencies by thematic analysis. Analysis using NVivo, this study identified five core teaching competencies challenges faced by vocational instructors in prison: planning and preparation competencies, classroom preparation competencies, carrying out professional responsibilities’ competencies; instruction competencies; and assessment competencies. This study can be useful to Prison Vocational Instructors, Prison Management and also Prison Institutions that pursue accreditation on TVET teaching and learning. Keywords: Teaching Competency; Education; Prison; TVET